Assessing the Impact of Mobility on COVID-19: Spatial Evidence from Ireland - O'Donoghue, Cathal; Geoghegan, Cathal; Kelly, Ruth; Kilgarriff, Paul (The Economic and Social Review, 2023)
This paper attempts to draw lessons from the Irish experience of COVID-19 by concentrating on the importance of mobility, especially the role of commuting. As lockdown periods progressed, we found increasing levels of workplace attendance, over and above what would be expected if only essential workers were physically going to work. Mobility-related variables were significantly associated with increased incidence of the virus at a national level. The level of inter-county essential worker commuting was found to be inversely related to infection rates in the workers’ home county.